Establishment of an Herbal Industry in India - Saini, Nadeep (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTIndian herbal market is one of the fastest growing market and may attain to 14500 crore by 2012. The herbal industry biz potential has revealed that currently the indian herbal market size is estimated at Rs. 7000 crore and over Rs. 3600 crore of herbal raw materials and medicines are exported by india. The herbal products become very popular now a days and found more application in medicinal treatment across the world. This review article focuses on current status of indian herbal industry. It also provides an insight on regulation of herbal industry in india.